2021
DOI: 10.3390/cells10092331
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases and Tissue Inhibitors of Metalloproteinases in Echinoderms: Structure and Possible Functions

Abstract: Echinoderms are one of the most ancient groups of invertebrates. The study of their genomes has made it possible to conclude that these animals have a wide variety of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs). The phylogenetic analysis shows that the MMPs and TIMPs underwent repeated duplication and active divergence after the separation of Ambulacraria (Echinodermata+Hemichordata) from the Chordata. In this regard the homology of the proteinases and their inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 145 publications
(258 reference statements)
0
6
0
Order By: Relevance
“…According to the authors, tensilins include a protein from Apostichopus japonicus (NCBI accession number PIK52999) [ 28 ] and one from the Cuvierian tubules of Holothuria forskali (NCBI accession number AQR59058), which we will mention below [ 29 ]. Later, the TIMPs of the echinoderms were classified into 5 groups [ 30 ]. The analysis showed that tensilins belong to group V of TIMPs.…”
Section: Tensilinmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the authors, tensilins include a protein from Apostichopus japonicus (NCBI accession number PIK52999) [ 28 ] and one from the Cuvierian tubules of Holothuria forskali (NCBI accession number AQR59058), which we will mention below [ 29 ]. Later, the TIMPs of the echinoderms were classified into 5 groups [ 30 ]. The analysis showed that tensilins belong to group V of TIMPs.…”
Section: Tensilinmentioning
confidence: 99%
“…It is possible that some TIMPs of echinoderms are neither stiffening proteins nor inhibitors of MMPs. Some TIMPs of echinoderms are assumed to have metalloproteinase-independent activities, as suggested in mammalian TIMPs [ 30 ].…”
Section: Tensilinmentioning
confidence: 99%
See 1 more Smart Citation
“…Metalloproteases (MMPs) are critical enzymes which are responsible for the degradation of the extracellular matrix (ECM) [108]. These proteases participate in various physiological processes, especially in connective tissue remodeling, such as the postpartum involution of the uterus, ovulation, and wound healing, and in pathological processes such as joint destruction in rheumatoid diseases [109,110]. It is known that metalloproteases are secreted as zymogens, and that they are activated proteolytically.…”
Section: Proteases and Hpv Carcinogenesismentioning
confidence: 99%
“…4 Due to the presence of matrix metalloproteinase tissue inhibitors (TIMPs) that inhibit its secretion, healthy skin contains extremely low levels of MMP-1, thereby retarding the breakdown of collagen (the main extracellular matrix backbone). [5][6][7] In addition, exposing skin to UV radiation produces reactive oxygen species (ROS) that damage the skin barrier and/or DNA. 8,9 Excessive accumulation of ROS leads to oxidative stress, which further accelerates premature skin aging.…”
Section: Introductionmentioning
confidence: 99%